2012
DOI: 10.1053/j.seminhematol.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Combination Therapy in Multiple Myeloma

Abstract: Bortezomib was approved for the treatment of multiple myeloma in 2003. Since then several bortezomib-based combination therapies have emerged. Although some combinations have been preceded by preclinical investigations, most have followed the inevitable process in which active (or potentially active) drugs are combined with each other to create new treatment regimens. Regimens that have combined bortezomib with corticosteroids, alkylating agents, thalidomide, and/or lenalidomide have resulted in high response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 51 publications
(51 reference statements)
4
54
0
3
Order By: Relevance
“…Researchers have observed promising preclinical activity with mapatumumab in patient with advanced solid cancers (Hotte et al, 2008). Currently, mapatumumab in combination with bortezomib in patients with refractory myeloma (Kapoor et al, 2012) and cisplatin and radiotherapyin patients with cervical cancer is in phase II clinical trials (Vici et al, 2014).…”
Section: Targeting the Extrinsic Pathwaymentioning
confidence: 99%
“…Researchers have observed promising preclinical activity with mapatumumab in patient with advanced solid cancers (Hotte et al, 2008). Currently, mapatumumab in combination with bortezomib in patients with refractory myeloma (Kapoor et al, 2012) and cisplatin and radiotherapyin patients with cervical cancer is in phase II clinical trials (Vici et al, 2014).…”
Section: Targeting the Extrinsic Pathwaymentioning
confidence: 99%
“…4 Despite such advancements, relapse following prolonged bortezomib treatment is inevitable due to either genetic modifications 5 or emergence of bortezomib-resistant plasma cell sub-clones. 6 Once myeloma cells acquire bortezomib resistance, they can no longer be treated with bortezomib. Clinical data shows that roughly half of initially bortezomib-sensitive MM patients do not respond to bortezomib once the disease is relapsed.…”
Section: Introductionmentioning
confidence: 99%
“…The proteasome inhibitor (PtdIns) bortezomib, approved for the treatment of MM by the FDA in 2003, 3 is one such debulking agent that has greatly contributed to improved outcomes observed in MM 4 Despite this advance, however, relapse following bortezomib therapy remains inevitable due to the emergence of bortezomib-resistant plasma cell sub-clones 5 For example; recent 'whole genome' sequencing studies of MM patients confirmed a high level of genetic heterogeneity; occurring both between separate patients, and within patient samples before and after therapy, 6 indicating the presence of a variety of genetically distinct plasma cell 'sub-clones' 7,8 Different subclones further indicate the presence of numerous minor tumor initiating cell populations with complex and divergent evolutionary histories. 9 The potential quiescence of these MM subclones, coupled with their diversity, can contribute to enhanced tumorigenicity and an intrinsic resistance to therapy.…”
Section: Introductionmentioning
confidence: 99%